Kloning Gen β-1,4 Glukanase dari Burkholderia cepaciake dalam Escherichia coli dan Karakterisasi Sekuennya - Fitriani Winangsih; Maria Bintang; Tri Puji Priyatno (Current Biochemistry, 2014)
The increasing of rice plant production has to deal with some constraints caused by pathogen infection such as by bacteria, viruses or fungi. Endophytic bacteria have antagonistic capacity against fungi and was used to prevent the invasion of the pathogen. Burkholderia cepacia is one of the endophytic bacteria carrying genes expressed in defense system against fungi by producing glucanase enzyme. The aim of this research was to clone a gene encoding β-1,4-glucanase from B. cepacia into the expression system in Escherichia coli. The clone of glucanase gene was isolated by PCR technique using DNA fragment of B. cepacia from rice plants. The Glu 1320 primer pairs were designed based on the glucanase gene nucleotide sequence on online database, with the length of the amplicon DNA of 1300 bp. Results from BlastN and BlastX analysis showed that the DNA fragment which was cloned into pGEM-T Easy vector had similarity with Endo-1,4-D-glucanase gene of Burkholderia mallei and Burkholderia pseudomallei. The identity of the cloned DNA fragment was 99% and E-value 0.0. Proteomic analysis of the amino acid sequence was done using Server Expasy Proteomic and the total of amino acid was 451 with, molecular weight of 48.363 kDa and isoelectric point (pI) of 5.87. The signal peptide had cleavage sites on position 23 and 24 in amino acid AAAAE. Recombinant protein clone was obtained from Protein Data Bank (PDB) database with the code of 4q2b.2.A. The protein consist of 349 residu which formed the secondary structure like of 7 betahairpin pairs, 20 turn, 3 helix-3/10, and 17 alpha-helix.